Sports participation and performance/productivity of UiTM students and staff / Prof. Madya Dr. Hjh. Rugayah Hj. Hashim … [et al.] - Hashim, Rugayah; Ahmad, Mustaza; Mazuki, Mohd. Anuar; Baharud-Din, Zulkifli (Research Management Institute (RMI), 2010)
The objective of this research is twofold: to evaluate the academic performance of students who are involved in sports and for the staff, to determine if UiTM staff who are involved in sports would have higher marks in their performance evaluation. The sample size for students were 1000 and for staff was 200. These are individuals who participation in the university held annual sports carnival. The response rate for students was 60.8% (608/1000) while for staff was 95% (190/200). Although Pearson's correlation output indicated that sports participation and work performance is not statistically significant (r=.049, p>.05), it was hypothesized that a positive relationship would exist between these two variables, that is higher participation in sports is associated with higher academic achievement or work performance. Thus, the correlation analysis for students showed that sports participation does not complement a student's academic achievement (r=.019, p>.05), and for the staff, sports participation and work performance is not statistically significant (r=.049, p>.05). Based on the empirical evidence, it is hoped that the university will revise its policy by emphasizing the need for its campus citizens to be more physically active as the benefits gained from being healthy would spill over into other aspects of the individual's existence such as better quality of life and wellness.